UTILITY OF ADRENAL VENOUS SAMPLING IN ACTH-INDEPENDENT CUSHING’S SYNDROME PRESENTING WITH BILATERAL ADRENAL ADENOMA - Aribon , Pamela Ann; Ejercito-De Jesus, Rowena (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Adrenocorticotropic Hormone (ACTH)-independent Cushing’s syndrome in a patient with bilateral adenoma poses a management challenge to clinicians. Utilization of adrenal venous sampling (AVS), as in this case, is instrumental in the precise localization of the functioning adenoma which will ensure the best management for these patients. CASE We report the case of a 67-year-old Filipino who presented with gradual weight gain for 3 months described as rounding of the face and increasing abdominal girth. The diagnosis of ACTH-independent Cushing’s syndrome was based on undetectable ACTH and an unsuppressed cortisol level by dexamethasone suppression test. CT scan revealed bilateral adrenal adenomas measuring 1.1 x 0.9 cm (APxT) in the right and 1.1 x 1.3 cm (APxT) in the left. AVS was done using cortisol levels adjusted by plasma aldosterone. This successfully lateralized the hypersecretion of cortisol to the left adrenal gland, hence a unilateral laparoscopic left adrenalectomy was done. Treatment was successful with post-operative laboratory confirmation of adrenal insufficiency. The patient was subsequently placed on glucocorticoid replacement until HPA axis recovery. CONCLUSION AVS adjusted by plasma aldosterone is a useful technique in localizing ACTH-independent CS in patients with bilateral adenoma to lateralize the lesion before planned surgery where unilateral adrenalectomy may be performed. Successful lateralization of the lesion may potentially spare the patient from lifetime or continuous corticosteroid replacement. In the unavailability of catecholamine or epinephrine, aldosterone ratio can be used to confirm success of adrenal vein cannulation.